The Effect of Demographic Factors on the Behaviour of Investors during the Choice of Investments: Evidence from Twin Cities of Pakistan (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: demographic factors; investors level of risk tolerance; correlation; pakistan